R2R3-MYB Transcription Factor NtMYB330 Regulates Proanthocyanidin Biosynthesis and Seed Germination in Tobacco (Nicotiana tabacum L.) - Zhao, Lu; Song, Zhongbang; Wang, Bingwu; Gao, Yulong; Shi, Junli; Sui, Xueyi; Chen, Xuejun; Zhang, Yihan; Li, Yongping (Frontiers in Plant Science, 2022)
Proanthocyanidins (PAs) are important phenolic compounds and PA biosynthesis is regulated by a ternary MBW complex consisting of a R2R3-MYB regulator, a bHLH factor and a WDR protein. In this study, a tobacco R2R3-MYB factor NtMYB330 was characterized as the PA-specific regulator in which the PA biosynthesis was promoted in the flowers of NtMYB330-overexpressing lines while decreased in the flowers of ntmyb330 mutants. NtMYB330 can interact with flavonoid-related bHLH partner NtAn1b and WDR protein NtAn11-1, and the NtMYB330-NtAn1b complex is required to achieve strong transcriptional activation of the PA-related structural genes NtDFR1, NtANS1, NtLAR1 and NtANR1. Our data reveal that NtMYB330 regulates PA biosynthesis in seeds and affects seed germination, in which NtMYB330-overexpressing lines showed higher PA accumulations in seed coats and inhibited germination, while ntmyb330 mutants had reduced seed coat PAs and improved germination. NtMYB330 affects seed germination possibly through two mechanisms: modulating seed coat PAs to affect coat-imposed dormancy. In addition, NtMYB330 regulates the expressions of abscisic acid (ABA) and gibberellin acid (GA) signaling-related genes, affecting ABA-GA crosstalk and seed germination. This study reveals that NtMYB330 specifically regulates PA biosynthesis via formation of the MBW complex in tobacco flowers and affects germination through adjustment of PA concentrations and ABA/GA signaling in tobacco seeds.